The Correlation between Risk Factors and Epstein-Barr Virus Serum Antibody with Histopathological Typing of Nasopharyngeal Carcinoma - Prasetyo, Awal; Sadhana, Udadi; Paramita, Dewi K.; Haryana, Sofia Mubarika; Hariwiyanto, Bambang; Sastrowijoto, Soenarto; Utoro, Totok (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The risk-combination of genetic or familial history, environmental risk factors, and EBV infection might cause nasopharyngeal carcinogenesis. The serum antibody for EBV IgA, namely, EBNA1+VCA-p18 has a good sensitivity as an early diagnostic test for nasopharyngeal carcinoma (NPC). AIM: This study aims to determine the correlation between risk factors and histopathological typing of NPC and also the correlation between the IgA [EBNA-1 + VCA p-18] ELISA and histologic type. METHODS: A cross-sectional method was used on 108 NPC patients which filled a questionnaire through an in-depth interview on the family condition to cancer, habit/lifestyle, and environmental risks. A total of 47 subjects were willing to donate blood samples for IgA [EBNA1 + VCA p-18] ELISA. Furthermore, Kendall’s tau-b (τ) correlation test was performed on NPC keratin type (WHO-1) and non-keratin (WHO-2 and 3). RESULTS: The results showed that the family history of non-keratinized NPC was associated with NPC WHO-3 as demonstrated by τ = 0.473, as well as salt-eating with τ = 0.334, smoked/grilled fish/meat eating τ = 0.205, instant noodle-eating τ = 0.356, consuming canned/packaged canned foods τ = 0.240, and flavored food eating habits τ = 0.364, along with passive smoking τ = 0.377, and chronic nasopharyngeal infection τ = 0.530. The IgA titers, namely, [EBNA1 + VCA p-18] ELISA for non-keratin type NPC was greater than the keratin type; however, it was not related to WHO-3 NPC as indicated by τ = 0.376, and p = 0.011 put this underlying before however. CONCLUSIONS: The positivity of IgA [EBNA-1 + VCA p-18] ELISA does not correlate with the non-keratin type histologic NPC, family history, as well as salt-eating, instant noodle, and flavored food eating habits, along with passive smoking and nasopharyngeal infection.